THE EFFECT OF FICUS CARICA L. (ANJIR) LEAF EXTRACT ON GENTAMICIN INDUCED NEPHROTOXICITY IN ADULT MALE ALBINO MICE - Ghafoor, Ammara; Tahir, Mohammad; Lone, Khalid Pervez; Faisal, Bushra; Latif, Waqas (Journal of Ayub Medical College Abbottabad, 2015)
Background: Gentamicin is an aminoglycoside isolated from Micromonospora purpurea known for its nephrotoxicity. Ficus carica L is known to treat many ailments. This study was designed to investigate the effects of Ficus carica L. (Anjir) leaf extract on renal oxidative stress induced by gentamicin in albino mice. Methods: In this laboratory based experimental study 30 mice were divided into three groups, containing 10 mice each. Group A being the control; groups B and C were experimental and treated with gentamicin 200 mg/kg/day intraperitoneally and, Ficus carica L. leaf extract 400 mg/kg/day orally with gentamicin 200 mg/kg/day intraperitoneally respectively for a period of 8 days. Blood samples were taken 24 hours after completion of the experimental period by cardiac puncture under anesthesia and kidneys of each mouse were taken out for microscopic examination. Results: Gentamicin treatment increased serum urea and creatinine levels (group B). Ficus carica L. leaf extract treated animals showed significant reduction in biochemical markers of kidney functions in group C. The histopathological examination of group A showed normal renal structure which was deranged in group B treated with only gentamicin, whereas, group C exhibited marked improvement in histological structure. Conclusion: Ficus carica L. leaf extract is effective in preventing gentamicin induced functional and structural changes in kidney of albino mice. Keywords: Gentamicin, Ficus carica (Anjir), Histopathology, Nephroprotection